Names of seasons as expressions of climatic conditions and agrarian practices - Hasiyatu Abubakari; Lawrence Sandow; Samuel Akugri Asitanga (Cogent Arts & Humanities)
Current changes in climatic conditions pose a threat to historical anecdotes associated with names of seasons among the Kusaas (native speakers of the Kusaal language) of Ghana. Historically, the weather patterns during specific periods were used as names for those periods creating a direct relationship between language and climatic conditions. However, this relationship is threatened by the rapid effect of climate change, which is resulting in changing weather patterns, breaking the synergy where names of seasons serve as direct descriptions of the climatic conditions of the respective periods. This study aims to document the names of the seasons in Kusaal, a language spoken in Ghana, highlighting their etymology, socio-cultural and economic significance and their accompanying climatic peculiarities. The study employs a qualitative research design with data gathered through semi-structured interviews with 12 native speakers of the language. Using content analysis, the study reveals that the Kusaas have four seasons: Sapal, Dɔnwalig, Sigir, and Tiŋdɔɔŋ. These names correspond with weather patterns, agrarian practices, and cultural events. The findings show a gradual shift to the adaptation of the Gregorian calendar which poses serious risk to indigenous climatic knowledge. The discussion is situated within the framework of linguistic relativity and cultural sustainability.